The Evaluators' Eye Impact Assessment and Academic Peer Review - Derrick, Gemma (Springer International Publishing, 2018)
This book offers an empirical analysis of how academic peer review panels mediate the traditionally non-academic criterion of societal impact. The UK's 2014 Research Excellence Framework (REF2014) for the first time included an "Impact" criterion that considered how research had influenced society, beyond academia. Using a series of interviews with REF2014 Main Panel A evaluators, the book explores how a dominant definition of Impact was constructed within panels and how this led to the development of strategies around valuing it as an ambiguous object. By doing so, Derrick brings a unique perspective to Impact that is currently overlooked in the dominant Impact evaluation discourse. Through examining the evaluation procedure as a dynamic process it is argued that the best models, strategies and insights for Impact evaluation are those constructed in practice, within peer review groups. By exploring the legitimacy of peer review as a tool to assess the societal impact of research, Derrick states that the future for Impact evaluation is not to seek alternative tools where peer review seemingly fails, but instead to highlight ways in which peer review panels can work smarter. The book will be essential reading for students, academics and policy-makers working in Education, as well as researchers interested in peer review processes and the research evaluation frameworks and audit exercises globally.